Pola Komunikasi Jarak Jauh Anak Dengan Orang Tua Mahasiswa Fakultas Ushuluddin Adab dan Dakwah IAIN Batusangkar - Irsandi Yudha; Adripen Adripen; Marhen Marhen (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2019)
The main problem in this study is the pattern of long-distance communication between children and parents. The pattern here is defined as the form, method, communication model used by FUAD IAIN Batusangkar students when communicating with their parents, and also the barriers to the child's long distance communication with parents. This study used descriptive qualitative method. The research informants were FUAD IAIN Batusangkar students who lived far from their parents. Data collection techniques that researchers use are observation, in-depth interviews. According to Sugiyono (2013: 245) data analysis in qualitative research carried out since before entering the field, during the field and after the field.  The results showed that the pattern of long-distance communication between children and parents of students of the Fakltas Ushuluddin Adab and Da'wah was a Stimulus-Response Communication Pattern in two Directions they experience and equally respond to what message they receive, and between them there is no limit to each other when communicating the point here is that in this communication process both communicators and communicants have the same position, so that the communication process can begin and ends where and whenever.